Quality of employment conditions and employment relations in Europe A report based on the fifth European Working Conditions Survey - Benach, Joan.; Vanroelen, Christophe; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
This report provides an in-depth analysis of the quality of employment conditions and employment relations in the European employed workforce. Employment in the report is viewed as the contractual relationship between an employer and a worker, specifically how the rights and duties embedded into the relationship are translated into real rights. The analysis is mainly based on data from the fifth European Working Conditions Survey (EWCS), conducted in 2010. Where appropriate, comparisons with earlier waves of the EWCS are made. An executive summary is also available.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of work life -- Europe; Labour relations; Politics and political science; Electronic books